A Social Movement Perspective on Finance: How Socially Responsible Investment Mattered - Arjaliès, Diane-Laure (Journal of business ethics, 2010)
This study discusses how social movements can influence economic systems. Employing a political–cultural approach to markets, it purports that ‘compromise movements’ can help change existing institutions by proposing new ones. This study argues in favor of the role of social movements in reforming economic institutions. More precisely, Socially Responsible Investment (SRI) movements can help bring SRI concerns into financial institutions. A study of how the French SRI movement has been able to change entrenched institutional logics of the French asset management sector provides wide-ranging support for these arguments. Empirical findings are drawn from a longitudinal case study (1997–2009), based on participative observation, interviews and documentary evidence. Implications for research on social movements, institutional change and SRI are outlined. Lastly, the study provides practitioners with some theoretical keys to understand the pros and cons of ‘SRI labels’.